Security in Wireless Sensor Networks: Issues and Security Mechanisms (International Journal of Current Engineering and Technology, 2014)
Wireless sensor networks are a new type of networked systems, characterized by severely constrained computational and energy resources, and an ad hoc operational environment. Wireless sensor network is highly vulnerable to attacks because it consists of various resources constrained devices with their low battery power, less memory, and associated low energy. Sensor nodes communicate among themselves via wireless links. However, there are still a lot of unresolved issues in wireless sensor networks of which security is one of the hottest research issues. This paper is an attempt to present a survey on the major topics in wireless sensor network security, and also present the obstacles and the requirements in the sensor security, classify many of the current attacks, and finally list their corresponding defensive measures.
Keywords: Wireless sensor networks, network security, attacks, defensive measures